2014
DOI: 10.3109/00016489.2014.880796
|View full text |Cite
|
Sign up to set email alerts
|

Surgical planning of Isshiki type I thyroplasty using an open-source Digital Imaging and Communication in Medicine viewer OsiriX

Abstract: All patients are free from dysphonia and their glottic closures have resolved satisfactorily. Postoperative CT revealed that appropriate implant positioning resulted in successful surgical intervention. The comparison of total operation time showed that with the new method, operation duration was shortened by 12 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Hiramatsu et al [14] reported that the 3D-CT images obtained while the glottis was closed (with phonation) and open could provide information about the reasons for unsatisfactory outcomes of laryngoplasty. In addition, Hara et al [15] demonstrated that preoperative determination of the window position in MT using digital imaging software-reconstructed 3D-CT images produced good vocal outcomes after MT. Indeed, in the present series of UVFP patients, laryngeal 3D-CT images could depict the position of the arytenoid cartilage, window, and implant, as well as the size of the implant and the degree of correction of the vocal fold, and the inter-rater reliabilities for all the factors were judged to be moderate or better.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Hiramatsu et al [14] reported that the 3D-CT images obtained while the glottis was closed (with phonation) and open could provide information about the reasons for unsatisfactory outcomes of laryngoplasty. In addition, Hara et al [15] demonstrated that preoperative determination of the window position in MT using digital imaging software-reconstructed 3D-CT images produced good vocal outcomes after MT. Indeed, in the present series of UVFP patients, laryngeal 3D-CT images could depict the position of the arytenoid cartilage, window, and implant, as well as the size of the implant and the degree of correction of the vocal fold, and the inter-rater reliabilities for all the factors were judged to be moderate or better.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, 3D-CT has been utilized to estimate the vocal fold condition in UVFP patients [12][13][14][15]. Yumoto et al [13] reported that 3D-CT endoscopic images could depict sagging/thinning and adduction/augmentation of the affected vocal fold before and after phonosurgery, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, the configuration model provided pivotal information in raising awareness about the customized treatment of unilateral vocal palsy patients. Hara et al 26 published the outcomes of using 3D CT image to predict vocal cord plane and optimal implant size, which resulted in reducing the operation time by 12 minutes. Our proposed 3D printed models not only provided a direct visualization of glottal configuration in different patients irrespective of the etiology or the severity of vocal cord palsy but also gave crucial information on the arytenoid cartilage’s condition, which made patient-tailored medialization laryngoplasty surgery possible.…”
Section: Discussionmentioning
confidence: 99%